Exploring The Influences on Cyber Education in a Bilingual Higher Institution - Wong, Simon (International Journal of Informatics and Information Systems, 2018)
This paper presents the research study which explores the variables influencing the learning effectiveness of the students taking an online introductory information technology course in cyber education in a bilingual higher education institution in Hong Kong. These variables are: (1) student's English proficiency, (2) instructor's guidance in an online discussion forum and (3) peer students' collaboration in an online discussion forum. Correlation analysis was adopted to identify whether any of these variables could be potential factors on the students 'learning performance while multiple regression analysis was performed to explore the combined effect of these variables on the students' learning performance. Validity and reliability of this research study are highlighted in this paper. Finally, the research findings are discussed.